1997
DOI: 10.1023/a:1000201017238
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Recent studies on the colony formation of soil bacteria opened the way to categorize soil bacteria into colony forming curve (CFC) groups of different growth rates. A bacterial culture collection comprising organisms from every CFC group is called an ecocollection (EC). Outlines of ECs of paddy soil 1992 and grassland soil 1987 and 1992 were described. Phylogenetic studies by 16S rDNA sequencing showed a great diversity of culture strains of the ecocollections. A set of alternative concepts was proposed; the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The soil enzymes results were found to be highly inconsistent and because of soil enzymes importance for the growth of microorganisms, these act as a good indicator of assessing the overall microbial activity (Dick, 1994). Many reports have showed that soil enzyme activities interacted positively with the diversity and productivity of plant communities, and increased with vegetation development (Hattori et al, 1997; Waldrop et al, 2000; Mamilov et al, 2001; Smith et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…The soil enzymes results were found to be highly inconsistent and because of soil enzymes importance for the growth of microorganisms, these act as a good indicator of assessing the overall microbial activity (Dick, 1994). Many reports have showed that soil enzyme activities interacted positively with the diversity and productivity of plant communities, and increased with vegetation development (Hattori et al, 1997; Waldrop et al, 2000; Mamilov et al, 2001; Smith et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Because of the staining methods used, only attached bacteria were studied and interstitial ones were not. However, in sediments and soils, the abundance of suspended bacteria is a few times or even orders of magnitude lower than that of the attached bacteria (Griebler et al., 2002; Hattori et al., 1997; Kuwae & Hosokawa, 1999). The mean size of attached bacteria (0.81 μm) corresponded to that reported in different sediments, for example, 0.51–0.56 μm (Griebler et al., 2002) or 0.19–1.68 μm (Mudryk & Podgórska, 2006).…”
Section: Discussionmentioning
confidence: 99%